Práticas de limitação de suporte de vida em uma Unidade de Terapia Intensiva Pediátrica : uma comparação de 30 anos - Furtado, Roiter de Albernaz (2020)
Introduction: With the evolution of medicine and the use of technologies, more and more we have patients who remain alive despite having irreversible diseases and poor prognosis. Studying and applying palliative care and life support limitation (LSL) has become essential. Objective: To establish the prevalence of LSL in patients admitted to the Pediatric Intensive Care Unit (PICU) and to deliberate how this care is performed. Methods: Retrospective study carried out in a tertiary PICU in Brazil. The study included patients aged from one month to 18 years who died. Patients diagnosed with brain death and those who stayed less than 24 hours in the PICU were excluded. Mode of death and variables correlated to LSL were described, and the group of patients who received LSL was compared with the group that did not receive. Results: During the study period, 53 patients were eligible, and the prevalence of description of LSL was 45.3%. Of the 24 patients who had LSL, only one did not have a do-not-resuscitate order. Life support withdrawn (LSW) was observed in half of the patients who underwent LSL. Age, length of PICU stay, presence of parents at the time of death and severity of illness on admission, obtained by the Paediatric Index of Mortality 2 (PIM2) score, were higher in patients who underwent LSL. Conclusion: LSL was associated with older and more severe patients. When comparing with other historical cohorts, our study showed an evident evolution in the prevalence of LSL and a significant evolution in the mode how this limitation is performed. In all cases the parents participated in the decision, and we observed a substantial increase in LSW.